Crustal structure of the French Guiana margin, west equatorial Atlantic - Greenroyd, C; Peirce, C; Rodger, M; Watts, A; Hobbs, R (2007)
Geophysical data from the Amazon Cone Experiment are used to determine the structure and evolution of the French Guiana and Northeast Brazil continental margin, and to better understand the origin and development of along-margin segmentation. A 427-km-long combined multichannel reflection and wide-angle refraction seismic profile acquired across the southern French Guiana margin is interpreted, where plate reconstructions suggest a rift-type setting. The resulting model shows a crustal structure in which 35-37-km-thick pre-rift continental crust is thinned by a factor of 6.4 over a distance of ∼70 km associated with continental break-up and the initiation and establishment of seafloor spreading. The ocean-continent boundary is a transition zone up to 45 km in width, in which the two-layered oceanic-type crustal structure develops. Although relatively thin at 3.5-5.0 km, such thin oceanic crust appears characteristic of the margin as a whole. There is no evidence of rift-related magmatism, either as seaward-dipping sequences in the reflection data or as a high velocity region in the lower crust in the P-wave velocity model, and as a such the margin is identified as non-volcanic in type. However, there is also no evidence of the rotated fault block and graben structures characteristic of rifted margins. Consequently, the thin oceanic crust, the rapidity of continental crustal thinning and the absence of characteristic rift-related structures leads to the conclusion that the southern French Guiana margin has instead developed in an oblique rift setting, in which transform motion also played a significant role in the evolution of the resulting crustal structure and along-margin segmentation in structural style. © 2007 The Authors Journal compilation © 2007 RAS.